ENGLISH AS A PAINFUL EXPERIENCE: NARRATIVES OF A YOUNG BRAZILIAN IMMIGRANT IN LONDON - Lima, Fernando Silvério (UNICAMP. Programa de Pós-Graduação em Linguística Aplicada do Instituto de Estudos da Linguagem (IEL), 2017)
ABSTRACT This study deals with personal experiences of a young female Brazilian immigrant learning English as a second language in London. Data were generated through narrative inquiry procedures, aimed at registering personal stories of the participant’s recollection of events. The results showed that learning English as a second language was a painful experience, especially at school, where the participant felt different for being an immigrant and not speaking the language which created a barrier to interact with other students. Also according to her, it appeared to be a reason to be bullied by her classmates. Despite such struggle, she was able to learn, acknowledging the support from her parents and daily interactions with people, rather than learning experiences in formal schooling.

RESUMO Este estudo lida com as experiências pessoais de uma jovem brasileira imigrante aprendendo inglês como segunda língua em Londres. Os dados foram gerados por meio de pesquisa narrativa, objetivando registrar histórias pessoais das lembranças dos eventos da participante. Os resultados revelam que aprender inglês como segunda língua foi uma experiência dolorosa, especialmente na escola, onde a participante se sentia diferente por ser imigrante e não falar a língua, criando uma barreira para interagir com outros alunos. Isso pareceu ser uma das razões, segundo ela, para ter sofrido bullying por parte dos colegas. Apesar de tal desafio, ela foi capaz de aprender, reconhecendo o apoio de seus pais e das interações cotidianas com as pessoas, ao invés das experiências de aprendizagem na escolarização formal.
INGLÊS COMO UMA EXPERIÊNCIA DOLOROSA: NARRATIVAS DE UMA JOVEM IMIGRANTE BRASILEIRA EM LONDRES
Keywords: Immigrant student; English as a second language; bullying; aluna imigrante; inglês como segunda língua; bullying.